Expression of Arabidopsis Hexokinase in Citrus Guard Cells Controls Stomatal Aperture and Reduces Transpiration - Lugassi, Nitsan; Kelly, Gilor; Fidel, Lena; Yaniv, Yossi; Attia, Ziv; Levi, Asher; Alchanatis, Victor; Moshelion, Menachem; Raveh, Eran; Carmi, Nir; Granot, David (Frontiers in Plant Science, 2015)
Hexokinase (HXK) is a sugar-phosphorylating enzyme involved in sugar-sensing. It has recently been shown that HXK in guard cells mediates stomatal closure and coordinates photosynthesis with transpiration in the annual species tomato and Arabidopsis. To examine the role of HXK in the control of the stomatal movement of perennial plants, we generated citrus plants that express Arabidopsis HXK1 (AtHXK1) under KST1, a guard cell-specific promoter. The expression of KST1 in the guard cells of citrus plants has been verified using GFP as a reporter gene. The expression of AtHXK1 in the guard cells of citrus reduced stomatal conductance and transpiration with no negative effect on the rate of photosynthesis, leading to increased water-use efficiency. The effects of light intensity and humidity on stomatal behavior were examined in rooted leaves of the citrus plants. The optimal intensity of photosynthetically active radiation and lower humidity enhanced stomatal closure of AtHXK1-expressing leaves, supporting the role of sugar in the regulation of citrus stomata. These results suggest that HXK coordinates photosynthesis and transpiration and stimulates stomatal closure not only in annual species, but also in perennial species.